Dror, a potential neurotrophic receptor gene, encodes a Drosophila homolog of the vertebrate Ror family of Trk-related receptor tyrosine kinases. - Wilson, C; Goberdhan, D; Steller, H (1993)
We have identified a Drosophila gene, Dror, which encodes a putative receptor tyrosine kinase (RTK) and maps to cytological location 31B/C on the second chromosome. In embryos, this gene is expressed specifically in the developing nervous system. The Dror protein appears to be a homolog of two human RTKs, Ror1 and Ror2. Dror and Ror1 proteins share 36% amino acid identity in their extracellular domains and 61% identity in their catalytic tyrosine kinase (TK) domains. Ror1 and Ror2 were originally identified on the basis of the similarity of their TK domains to the TK domains of members of the Trk family of neurotrophin receptors. The Dror protein shows even greater similarity to the Trk proteins within this region than do the human Ror proteins. In light of its similarity to trk and its neural-specific expression pattern, we suggest that Dror may encode a neurotrophic receptor that functions during early stages of neural development in Drosophila.